2002
DOI: 10.1002/1521-3803(20020301)46:2<92::aid-food92>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soaking, germination, cooking and fermentation on antinutritional factors in cowpeas

Abstract: The present work deals with the study of efficacy of some treatments, namely soaking (in water and bicarbonate solution), ordinary and pressure cooking, germination and fermentation in reducing or removal of antinutritional factors usually present in cowpeas (protease inhibitors, tannins, phytic acid and flatus-producing oligosaccharides (raffinose and stachyose). The results showed that long-time soaking (16 h) in bicarbonate solution caused remarkable reduction in the antinutritional factors. Pressure cookin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
86
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 28 publications
18
86
4
Order By: Relevance
“…4). Similar results were obtained in studies on germinating seeds of other plants (Elmaki et al 1999;Mbithi-Mwikya et al 2000;Ibrahim et al 2002;Mubarak 2005). None- Vertical bars represent ± SE from three independent experiments.…”
Section: Discussionsupporting
confidence: 84%
“…4). Similar results were obtained in studies on germinating seeds of other plants (Elmaki et al 1999;Mbithi-Mwikya et al 2000;Ibrahim et al 2002;Mubarak 2005). None- Vertical bars represent ± SE from three independent experiments.…”
Section: Discussionsupporting
confidence: 84%
“…Onigbinde & Akinyele (1983) reported a 46% reduction in raffinose and a 50% reduction in stachyose contents after boiling for 40 min. Ibrahim, Habiba, Shatta, & Embaby (2002) reported that cooking in boiling water for 40 min with a water-to-seed ratio of 10:1 (w/w) resulted in a 100% loss of raffinose and an 81% loss of stachyose.…”
Section: Experimental Changes In Alpha-galactosides During the Soakinmentioning
confidence: 99%
“…Common cooking practices reduce, but do not eliminate, the phytic acid content of pulses [12,34,35].…”
Section: Other Compounds+indexesmentioning
confidence: 99%